An Extended Analytical Approach to Evaluating Monotonic Functions of Fuzzy Numbers - Arthur Seibel; Josef Schlattmann (Advances in Fuzzy Systems)
This paper presents an extended analytical approach to evaluating continuous, monotonic functions of independent fuzzy numbers. The approach is based on a parametric α-cut representation of fuzzy numbers and allows for the inclusion of parameter uncertainties into mathematical models.